Are the green projects in line with the Maqasid Shariah? an assessment of green firms in Bangladesh - Julia, Taslima; Kassim, Salina; Engku Ali, Engku Rabiah Adawiah (International Research Centre of Islamic Economics and Finance (IRCIEF), 2018)
The regulators and policy makers of Bangladesh are very much aware about the impact of climate change and pollution on the economy and quality of life of the citizens. This concern is manifested by the efforts to introduce the green banking policy and guidelines where green practices are promoted among the investors, financiers and businessmen. However, there is a lack of investigation of the performance of the projects, which are classified as “green” according to the Bangladesh central bank policy. As an extension to our earlier work which has elaborated on the shariah-compliancy of the green banking policy of Bangladesh, this paper aims to explore the shariah-compliancy of the green businesses. In methodology, we consider the Maqasid Shariah parameters and design survey questionnaires to be administered on five green companies to confirm the preset themes on Maqasid Shariah. The sample firms sourced their financings from various shariah-based banks’ green financing scheme. The collected data is analyzed following deductive thematic analysis approach and it is ascertained by respondents of the green companies that sustainability of green firms is positively related to the Maqasid Shariah and green firms’ activities are in line with Shariah.